The Mosaic Theory of Natural Complexity : A scientific and philosophical approach - Georges Chapouthier (Éditions des maisons des sciences de l'homme associées, 2018)
What is complexity? The present work will offer a description of complex systems based on two general principles: juxtaposition of similar units and then integration of these units, once modified, into structures at a higher level of which they become parts. As in a mosaic, however, these parts within the higher level or structure, retain some independent properties and autonomy. The model is based directly on observations of living organisms: cells or organs retain their autonomy functioning within a given organism, and individual organisms have autonomy when functioning as part of a population or society.